Evaluation and visualization of multiaxial fatigue behavior under random non-proportional loading condition - Takahiro Morishita; Fumio Ogawa; Takamoto Itoh (Fracture and Structural Integrity)
In cyclic multiaxial stress/strain condition under nonproportional loading in which principal direction of stress/strain are changed in a cycle, it becomes difficult to analyze stress/strain ranges because of complexity of multiaxial stress/strain states depending on time in cycles. In order to evaluate stress/strain simply and suitably under non-proportional loading, Itoh and Sakane have proposed a method called as IS-method and a strain parameter for life evaluation under non-proportional loading NP. In the method, 6-components of stress/strain are converted to an equivalent stress/strain indicating the amplitude and the direction of principal stress/strain as a function of time as well as an intensity of loading nonproportionality fNP. Based on IS-method, the authors also have developed a tool which enables to analyze multiaxial stress/strain condition with the nonproportionality of loading history and evaluate failure life under nonproportional multiaxial loading. The tool indicates the analyzed results on monitor and users can understand visually not only variation of the stress/strain conditions but also non-proportionality during the cycle, which helps the design of material strength.